Black and White Feminism, a Post-Colonial Vision - Hutchison, Mireille (CIENCIA ergo-sum; Vol. 5 Núm. 3 (1998): CIENCIA ergo-sum (noviembre 1998-febrero 1999), 2017)
This article will analyze the differences between the needs of all women in the North and in the South. It will examine the exclusion of colored women in Western feminism, although not all-western women are White. It will analyze some domination issues within the feminist movement, its reasons, and the possibilities, within the context of Post Colonial Studies.